Pengaruh Perceived Service Quality dan Customer Satisfaction pada Service Loyalty yang Dimoderasi oleh Variety Seeking - Hidayanti, Ida (Jurnal Widya Manajemen & Akuntansi, 2006)
The purpose of this research is to test the influence of perceived service quality and customer satisfaction on service loyalty that moderated by variety seeking. The objectives of this research are to examine : (a) the effect of perceived service quality on service loyalty (b) the effect of perceived service quality on customer satisfaction (c) the effect of customer satisfaction to service loyalty (d) there is a positive influence of customer satisfaction as a mediator (e) there is a positive inJlaerce of wiety seeking as a m&ranr ofitc relattorchip betwien artomer utisfaction otd sedce loyol$. The conclusion of the result itwws ttnt anoner Wisfaction is a nwdiating +wiable od vwiety seeking is a moderating vtiable.